Factors associated with patient activation among individuals with depression within racial/ethnic groups in the United States - M. Janelle Cambron-Mellott; Nate Way; Jacqueline Pesa; Muideen Adigun; H. Jean Wright II (Preventive Medicine Reports, 2023)
Increasing patient activation may be vital for improving quality of care for individuals with depression. Among adults with depression who reside in the United States, we sought to examine the association of depression severity, race/ethnicity, and household income with patient activation and within identify factors associated with patient activation within race/ethnicity groups. Data from the 2020 US National Health and Wellness Survey, a cross-sectional, general population survey, were used to identify White, Black/African American, Asian, and Hispanic respondents with self-reported physician-diagnosed depression. Generalized linear models were used to identify factors associated with patient activation. Analyses included 8,216 respondents (mean age = 44 years, 68.0% female). Depression severity was negatively associated with patient activation (β = −0.29, p < 0.001). Patient activation was significantly higher in Black vs. White respondents (β = 1.50, p = 0.001) and in respondents with a household income of $25,000–$49,999 (β = 0.96, p = 0.015), $50,000–$99,000 (β = 0.88, p = 0.031), and ≥$100,000 (β = 1.78, p < 0.001) vs. <$25,000. Adjusted mean patient activation scores were highest among Black respondents (61.1), followed by Hispanic (60.2), White (59.6), and Asian (59.0) respondents. Neither race/ethnicity nor household income moderated the relationship between depression severity and patient activation; however, the factors most strongly associated with patient activation differed by race/ethnicity. These results indicate that the pathway to improving patient activation in individuals with depression may vary by race/ethnicity. Understanding factors associated with patient activation can help inform the design of interventions to increase patient activation in individuals with depression.